(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2015)
Customers play a vital role in the growth and development of Insurance Sector in developing countries like India. It is important for the insurance providers to market themselves in a way that they attract new customers as well as retain the old ones. For this, customer orientation or customer centricity is the key. Customers’ satisfaction should be the foremost agen da for marketers so as to attract and retain the customers which would also help them in remaining competitive in the current global arena. This paper attempts to identify the major areas of customers’ grievances/ com plaints in non life insurance business in India and attempts to categorise these complaints as a part of different Marketing Mix elements. This pa per further examines the role of Insurance Regulatory and Development Authority of India and insurance companies in providing a solution to resolve these complaints.